The effects on production of milking crossbred suckler cows grazing a semi-arid area of Kenya. II - The performance of calves from birth to weaning - Anindo, D.O.; Topps, J.H. (1993)
Three experiments were conducted in successive years using 32, 53 and 74 calves of crossbred suckler cows in a semi-arid area close to Nairobi, Kenya. A 2 X 2 factorial experimental design was used with milking and supplementation (2 kg concentrate/head per day) as the main treatments. The effects of milking (or not milking), supplementing (or not supplementing) cows were examined by measuring the growth rate of the calves from birth to weaning at 6 months of age. In experiments 2 and 3 each of the 4 groups of calves was sub-divided to give equal numbers of calves either receiving or not receiving a small amount (<less or =>1 kg/day) of weaner pellets. The growth rates for calves of milked cows were 0.54 kg/day (experiment 1), 0.63 kg/day (experiment 2) and 0.58 kg/day (experiment 3). The growth rates of calves of the non-milked cows were 0.81 kg/day (experiment 1), 0.70 kg/day (experiment 2) and 0.67 kg/day (experiment 3). Provision of concentrate to either the cows and/or the calves did not have a significant effect on the growth of the calves except in the first 12 weeks of experiment 1. Therefore, although withdrawal of milk from crossbred suckler cows significantly reduced the growth rate of the calves, acceptable weights at weaning in the range of 120 to 140 kg were obtained.